The News in context news reading and political consciousness - Bernabe, Corina D.; University of the Philippines Diliman College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2000)
This is an exploratory study in the role of news in people's everyday lives and how readers go about reading, interpreting and utilizing the news in their own social and in the larger political context. The study used a variety of theories, the schema theory being the principal component of the framework. Schemata are the carriers basic belief structures, determined by past experiences and past news reception, that people use in approaching a given article of news. A combination of indigenous methodology, specifically pagtatanong-tanong and pakikipagkwentuhan; and focus interviews were used for the study. These methods were particularly well suited given the study's topic and objectives. The study discovered that most people pay attention to the news only in a general and casual way, but that they nevertheless manage to stay relatively well informed because of the pervasiveness of news and news reading in everyday life. Most people recognize the importance of news and feel the need to be constantly informed, even though the pressures of daily life may prevent them from being so. Even when awareness was not a problem, people seldom were able to apply their knowledge on news to the larger arena of participatory democracy. However, they were generally more able to find some personal relevance to certain news and relate it to their own lives. People use a variety of schemata in processing news information. Most of these schemata had political and human-interest overtones. Lifestyle and social status, plus media influence, was the factors likely to influence the quality and direction of the schema to be adopted by the readers. Because they view most news as old hat, especially those concerning politics, they rarely make major modifications to their established schemata. The role and nature of conversation and social interaction was also explored. It was revealed that people talk about the news mostly in bare terms and seldom get involved in in-depth discussion except among readers who had a high level of involvement in the news. Otherwise, news-conversation plays mostly a social role, serving to increase knowledge, exchange opinions, and pass the time.
Vita.
Thesis (A.B. Communication Research)--University of the Philippines Diliman
Keywords: Attribution of news -- Philippines; News audiences -- Philippines